The Correlation of Y Chromosome Microdeletion Screening and G-Banding Chromosomal Analysis in Adult Males - Kristianingrum, Rosiana; Ni Luh Gede Puspita Yanti; Moh. Fairuz Abadi (CV. CENDIKIA JENIUS INDONESIA, 2025)
Male infertility is a reproductive health problem often associated with genetic abnormalities, such as Y chromosome microdeletions and chromosomal aberrations detectable through G-banding analysis. This study is important since research on the relationship between these two examinations in evaluating male infertility in Indonesia is still limited. The purpose of this study was to analyze the correlation between Y chromosome microdeletion and G-banding chromosomal analysis in adult males.This study employed a cross-sectional correlational design, involving 46 adult males with a history of infertility examined at the Prodia National Reference Laboratory between January 2023 and April 2025. Samples were collected using a total sampling technique. Y chromosome microdeletion was examined using multiplex PCR, while chromosomal analysis was conducted using the G-banding technique. Data were analyzed descriptively and with the Spearman correlation test using SPSS version 27.The results showed that 97.83% of subjects had normal Y chromosome microdeletion results, while 2.17% presented AZFc deletions. G-banding analysis revealed 91.30% normal karyotypes and 8.70% chromosomal abnormalities, including Klinefelter syndrome. The Spearman test indicated no significant correlation (r = -0.046; p = 0.761).It is concluded that both examinations assess different genetic aspects but are complementary. Clinicians are advised to use both methods in evaluating male infertility, and further studies with larger samples are recommended.